New psychoactive substances: a review and updates - Abu Shafi; Alex J. Berry; Harry Sumnall; David M. Wood; Derek K. Tracy (SAGE Publishing, 2020)
New psychoactive substances (NPS) are a heterogeneous group of substances. They are associated with a number of health and social harms on an individual and societal level. NPS toxicity and dependence syndromes are recognised in primary care, emergency departments, psychiatric inpatient and community care settings. One pragmatic classification system is to divide NPS into one of four groups: synthetic stimulants, synthetic cannabinoids, synthetic hallucinogens and synthetic depressants (which include synthetic opioids and benzodiazepines). We review these four classes of NPS, including their chemical structures, mechanism of action, modes of use, intended intoxicant effects, and their associated physical and mental health harms. The current challenges faced by laboratory testing for NPS are also explored, in the context of the diverse range of NPS currently available, rate of production and emergence of new substances, the different formulations, and methods of acquisition and distribution.